New approaches in bonding to glass-ceramic: Self-etch glass-ceramic primer and universal adhesives - Maier, Eva; Bordihn, Vivien; Belli, Renan; Taschner, Michael; Petschelt, Anselm; Lohbauer, Ulrich; Zorzin, José Ignacio (Journal of Adhesive Dentistry, 2019)
Purpose: To investigate the tensile bond strength of silane-containing universal adhesives and self-etch glass-ceramic primer to lithium disilicate glass ceramics (LS2). Materials and Methods: 960 rectangular LS2 bars (7 mm x 3 mm x 9 mm, IPS e.max CAD, Ivoclar Vivadent) were manufactured and divided into 4 groups (n = 240). Group 1 was etched with 5% hydrofluoric acid (HF) for 20 s (VITA Ceramics Etch, Vita Zahnfabrik), group 2 was etched with 5% HF for 20 s and silanized (ESPE Sil, 3M Oral Care), group 3 was pre-treated with a self-etching glass-ceramic primer (Monobond Etch & Prime, Ivoclar Vivadent, and group 4 received no pre-treatment. Three universal adhesives (iBOND Universal, Heraeus Kulzer; Scotchbond Universal Adhesive, 3M Oral Care; Futurabond U, Voco) were applied to the differently pre-treated surfaces, with Heliobond (Ivoclar Vivadent) serving as control. The bars from each group were paired and luted perpendicularly, forming a square bonded area of 9 mm2, using Variolink II (Ivoclar Vivadent) with a constant pressure of 10 N, followed by light curing (40 s at 800 mW/cm2, Elipar Trilight, 3M Oral Care). The resulting specimens were stored for 24 h at 37°C in distilled water. Half of the specimens of each group were submitted to tensile bond strength testing, the other half were thermocycled ([TC] 5000 cycles, 5°C/55°C, 30-s dwell time) before testing. Data were analyzed using three-way ANOVA (α = 0.05). Results: Group 2 (HF etched and silanized) and group 3 (self-etching glass-ceramic primer) reached significantly higher mean bond strengths than did groups 1 (only HF etched) and 4 (no pre-treatment). Conclusion: Additional silanization of HF-etched LS2 statistically signficantly improved the tensile bond strength of the silane-containing universal adhesive (Scotchbond Universal). The self-etching glass-ceramic primer Monobond Etch & Prime achieved mean bond strengths that did not differ significantly from HF-etched and silanized specimens.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Lithium disilicate ceramic; Self-etch glass ceramic primer; Silanization; Tensile bond strength; Universal adhesive